The Effect of Changes in the Ship's Center of Gravity on Ship Stability on the MV. Meratus Larantuka - Pramanda Yuliananta; Capt. Firdaus Sitepu; Dian Junita Arisusanty; I'ie Suwondo (International Journal of Science and Environment (IJSE), 2026)
Ship stability failure contributes significantly to global maritime accidents, particularly container ship capsizing due to cargo shift and ballast imbalance. This study analyzes the effect of changes in the center of gravity (G) on ship stability on the MV Meratus Larantuka, a domestic feeder container ship on the Eastern Indonesia route. Using a descriptive qualitative methodology, data collection included participatory observation of the loading and unloading process, clinometer readings, draft measurements, and semi-structured interviews with four senior officers (Master, Chief Officer, Chief Engineer, OOW) during sea practice in January 2026. Data analysis followed the Miles and Huberman model with iterative reduction-presentation-verification and source triangulation. The findings revealed that bay plan deviation caused a transverse shift of G of 1.2 meters, unbalanced ballast resulted in a virtual increase of G of 0.35 meters through the free surface effect, and uneven freshwater consumption triggered a 0.5 meter trim by bow. Stability calculations showed a reduction in GM from 0.85 m to 0.62 m with a 12 percent loss of GZ curve area, although remaining within IMO criteria through counter-ballasting. The conclusions emphasized optimization of real-time PlanMaster and daily ballast rotation SOPs to reduce the stability risk by 50 percent on the choppy Sulawesi route.